Hell house or something more? Horror, abjection and mental illness. (1st November 2019) - Sheldon, Zachary
AbstractMany theorists argue that abjection is at the core of the experience and fascination of the horror genre. Abjection relates to the simultaneous attraction and revulsion that audiences feel around the horrific, gory or disturbing subjects that comprise the focus of horror films. Some recent horror media have centred on the gendered components of abject theory, notably the relationship of a mother to her children, as well as the stigma surrounding mental illness. These films transform motherhood into an abjection tied intimately to depression and ultimately suggest ways for audiences to make sense of both depression and conceptions of abject motherhood. This article examines Netflix's The Haunting of Hill House (2018) for its contribution to this ongoing discussion, arguing that the series takes advantage of the camera's ability to surveil its subjects in order to suggest ways that a mother's abjection and mental illness suffuse the network of familial and social relations that she is caught up in. In this, the series' horrific surveillance of its characters provides varying discursive resources with which the audience may evaluate and act regarding their own experiences of depression and abject motherhood.